Answer:
y = 2(x+3)(x-3)
Step-by-step explanation:
y = a (x-x1) * (x-x2) * (x-x3) * ... (x-xn)
x 1 to n represents the roots
Answer:
1.one solution is the answer
Step-by-step explanation:
Answer:
thank you
Step-by-step explanation:
Answer:
The table represents a function.
What is the value of f(-1)?
f(-1) = - 3
f(-1) = -1
f(-1) = 0
f(-1) = 6
Step-by-step explanation:
Answer:
$100
Step-by-step explanation:
when you read the context you have your friend which is (1), than she asks (You (1) and (Two (2) other friends to help.
Add
Friend + You + Two other friends= 4
Now Divide 100/4= 25
hope this helps